Nucleic acid detection using a universal electrochemical sensor for SNS differentiation - Calvo-Marzal, Percy (2018)
Nucleic acid detection with high sensitivity and selectivity capabilities could aid in the diagnosis of varies diseases such as: infections, cancer, among others. Discrimination of a mismatch or single nucleotide substitution (SNS) is challenge due to a minimum pair to pair formation double strand needed to stabilize the structure. Here we present a new approach to atinge the needed stability by using additional segments strains to favored stabilization. The use of additional complementary strains facilitates the discrimination of a SNS in a cooperative way.